2013
DOI: 10.1007/s10792-013-9799-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pterygium morphology on fibrin glue conjunctival autografting pterygium surgery

Abstract: To evaluate the influence of pterygium morphology on the efficacy and safety of fibrin glue in pterygium surgery with conjunctival autografting. A prospective case series. During a period of 15 months, 45 patients (51 eyes) were recruited from the General Hospital for pterygium surgery. Seven eyes (13.73 %) were operated on for a recurrent pterygium. Autologous conjunctiva was harvested from the superior bulbar conjunctiva and fixed with fibrin glue. The pterygia were preoperatively divided into atrophic/grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…From previous literature, it is understood that pterygium size and grade increases the risk of recurrence [25][26][27]. In our cases, it cannot be determined if attendings selected the more complex and higher grade cases.…”
Section: Discussionmentioning
confidence: 82%
“…From previous literature, it is understood that pterygium size and grade increases the risk of recurrence [25][26][27]. In our cases, it cannot be determined if attendings selected the more complex and higher grade cases.…”
Section: Discussionmentioning
confidence: 82%
“…Finally, the follow-up duration in some studies included in the present review might not have been sufficient. Reports showed that 50% of recurrences might occur with in 4 months, and 97% might occur within 12 months [ 62 , 63 ]. Thus, follow-up of at least 1 year is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Sandra et al reported that the use of fibrin glue was a safe, easy and effective technique for attaching the conjunctival autograft in pterygium surgery and the morphology of pterygium influenced recurrence rates, without significant intraoperative and postoperative complications. 22 Shehadeh-Mashor et al reported that pterygium excision and conjunctival autograft using fibrin glue to secure the graft combined with intraoperative mitomycine C seems to be a safe and effective surgical option for treating recurrent pterygium. 23 When the two components of the fibrin glue are applied simultaneously, a fibrin clot forms within approximately 30 seconds.…”
Section: Discussionmentioning
confidence: 99%